Coincidence of Congenital Diaphragmatic Hernia and Arnold Chiari II Malformation: A Case Report (Nepalese Journal of Radiology, 2012)
Congenital diaphragmatic hernia is the developmental abnormality in which abdominal viscera herniate into the thoracic cavity through defect in the diaphragm. Almost 10% of congenital diaphragmatic hernia has associated central nervous system malformation including anencephaly, myelomeningocele and hydrocephalus. The Arnold-Chiari malformation is a congenital abnormality of Central Nervous System (CNS), characterized by downward displacement of the parts of the cerebellum, fourth ventricle, pons and medulla oblongata into the spinal canal. Here we present an extremely rare case with coexistent congenital diaphragmatic hernia and Arnold Chiari II malformation occurring in a viable fetus of 20 weeks gestational age. NJR I VOL 2 I ISSUE 1 46-49  Jan-June, 2012 DOI: http://dx.doi.org/10.3126/njr.v2i1.6981